2005
DOI: 10.1016/j.febslet.2005.07.045
|View full text |Cite
|
Sign up to set email alerts
|

The dinuclear iron‐oxo ferroxidase center of Pyrococcus furiosus ferritin is a stable prosthetic group with unexpectedly high reduction potentials

Abstract: Recombinant ferritin from Pyrococcus furiosus expressed in Escherichia coli exhibits in EPR monitored redox titrations a mixed valence (Fe 3+ -Fe 2+ ) S = 1/2 signal at intermediate potentials that is a high-resolution homolog of the ferroxidase signal previously described for reconstituted horse spleen apo-ferritin. P. furiosus reconstituted apo-ferritin reduced to intermediate potentials exhibits the same mixed-valence signal, which integrates to close to one spin per subunit. The reduction potentials of +21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…The PfFtn FC followed the common trend, and as mentioned already the occupation of FC sites B and C was only observed in Fe-soaked or Zn-soaked crystals. This contradicted our EPR studies that showed a fully developed dinuclear iron FC EPR signal in the sample prior to crystallization [39]. In order to check the integrity of the PfFtn FC, we loaded three samples of apo PfFtn with iron and incubated them for 1 day and 2 months at 4 °C in air and, mimicking the crystallization conditions, for 2 months in a 2 M ammonium sulfate solution at room temperature.…”
Section: Resultsmentioning
confidence: 65%
“…The PfFtn FC followed the common trend, and as mentioned already the occupation of FC sites B and C was only observed in Fe-soaked or Zn-soaked crystals. This contradicted our EPR studies that showed a fully developed dinuclear iron FC EPR signal in the sample prior to crystallization [39]. In order to check the integrity of the PfFtn FC, we loaded three samples of apo PfFtn with iron and incubated them for 1 day and 2 months at 4 °C in air and, mimicking the crystallization conditions, for 2 months in a 2 M ammonium sulfate solution at room temperature.…”
Section: Resultsmentioning
confidence: 65%
“…the invariant metallic motive constituted by iron atoms bridged by a peroxo group, which are permanently bound to specific amino acids of the protein, is a stable prosthetic group and that after formation of a stable diiron center, iron(II) is oxidized on its way to the core by the iron(III) in the ferroxidase center, and electrons are transferred to O2 [57]. EPR [58] and kinetic studies [59] support this assumption.…”
Section: Ferritin Iron Uptakementioning
confidence: 58%
“…c The specific activity of the slow oxidation phase attributed to the core formation versus the Zn(II)-to-ferritin ratio. The specific activity was calculated using an extinction coefficient of 2.5 cm −1  mM −1 [21]…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of a recent paramagnetic-NMR study by Turano et al [20] using bullfrog M-chain ferritin, it has been proposed that with a transient FC substrate site, the Fe(III)–O–Fe(III) product leaves the FC and passes through a channel system in the protein shell, forming transient clusters of increasing nuclearity, and only after oxidation of an approximately 150–200 Fe(II) per protein does the core formation process start. In contrast, recent EPR [21] and kinetic studies [22] have suggested that the FC of the non-heme ferritin from the hyperthermophilic archaeal anaerobe Pyrococcus furiosus (PfFtn) is a stable prosthetic group. We have proposed that after formation of a stable diiron center, Fe(II) on its way to the core is oxidized by the Fe(III) in the FC, and electrons are transferred to another oxidant such as molecular oxygen [22].…”
Section: Introductionmentioning
confidence: 99%